PERKEMBANGAN NOVEL ISLAM PRESPEKTIF GENDER - Suwartini, Iis; Fujiastuti, Ariesty (Universitas Andalas, 2020)
The development of Islamic novel is increasingly diverse. Gender is one of the topics that writers often pick up. The closeness of the theme with the reader is one of the reasons for the development of gender perspective Islamic novel. This study aims to describe the development of Islamic gender perspective novel using literature studies. Data obtained from reviewing documents in the form of books and literature. The results of the study show that a gender perspective is used by many authors in bringing up Islamic novel. Gender perspectives are reflected in the main ideas of feminism in the novel, including: the interpretation of society against the subordination of women; the position of women in marriage; the position of women in education and careers.